Pengaruh Advertising Attractiviness, Influencer Marketing, Dan Online Customer Review Terhadap Keputusan Pembelian Somethinc (Studi Kasus Mahasiswa FEB UNISMA Angkatan 2020) - Taqiyyah, Farah Maulidah; Khalikussabir, Khalikussabir; Millaningtyas, Restu (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to analyze the impact of Advertising Attractiveness, Influencer Marketing, and Online Customer Reviews on the Purchase Decision of Somethinc products. The research employs a quantitative method with a population of students from the Faculty of Economics and Business, Universitas Islam Malang, class of 2020, who have previously purchased Somethinc products. Purposive sampling was used to determine the sample, with a total of 87 respondents calculated using the Slovin formula. Primary data was collected through questionnaires distributed to the respondents.The results indicate that, simultaneously, Advertising Attractiveness, Influencer Marketing, and Online Customer Reviews have a significant impact on the Purchase Decision of Somethinc products. Partially, Advertising Attractiveness has an impact but is not significant in influencing the Purchase Decision of Somethinc, whereas Influencer Marketing and Online Customer Reviews significantly affect the Purchase Decision of Somethinc. The coefficient of determination (R2) shows that 60% of the variation in Purchase Decisions can be explained by Advertising Attractiveness, Influencer Marketing, and Online Customer Reviews, while the remaining 40% is explained by factors outside this model. Keywords: Advertising Attractiveness, Influencer Marketing, Online Customer Reviews and  Purchase Decision.